Estimation of the surface area-to-volume ratios of litter components of the Brazilian rainforest and their impact on litter fire rate of spread and flammability - Bufacchi, Paulo; Santos, José Carlos; de Carvalho, João Andrade [UNESP]; Krieger Filho, Guenther Carlos (Springer Nature, 2020)
The surface-area-to-volume ratio (SAV) is a significant parameter in vegetation description, although different researchers have presented diverging estimates for forest litter. However, considering litter as a unique entity and disregarding the SAV of its components provides a misleading fire rate of spread. Undoubtedly, the leaves are more relevant than the twigs for the rate of spread of surface fires, as the former has a higher SAV. Therefore, based on the proven hyperdominance of tree species in the Brazilian rainforest, this work presents an accurate method to estimate the SAV. Furthermore, it demonstrates the critical role played by the SAV in the litter flammability and fire rate of spread assessments and shows that the leaf moisture content does not influence its SAV. Besides, comparing SAV data using the methodology presented herein with other authors’ assessments, the results differ by up to 49%. Finally, using the Brazilian rainforest litter in the methodologies of two distinct authors showed a difference of at least 36% in the results. The primary outcome of this study is the estimation of the SAV of leaves and thin, medium, and thick twigs, representative of the Brazilian rainforest, at 12,680 m−1, 1360 m−1, 620 m−1, and 310 m−1, respectively. The estimated SAV values are essential input data to numerical simulation models, and for comparison purposes with other authors’ work, the litter SAV is 8460 m−1.
Keywords: Brazilian rainforest; Flammability; Litter; Rate of spread; Surface-area-to-volume